2015
DOI: 10.12688/f1000research.6638.1
|View full text |Cite
|
Sign up to set email alerts
|

CPIRD: A successful Thai programme to produce clinically competent medical graduates

Abstract: The programme titled “Collaborative Project to Increase Production of Rural Doctors” (CPIRD) is a rural medical education project launched in 1994 in Thailand. This study aimed to compare the academic performances in medical study over five years and the pass rates in national medical license examinations (MLE) between students enrolled in CPIRD and two other tracks.Grade point average (GPA) over five years and results of MLEs for four cohorts of students enrolled from 2003 to 2006 in Prince of Songkla Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 33 Previous studies suggests that medical teaching in service hospitals may also help equip students with better clinical competency as compared to teaching in large university hospitals. 33 - 35 Training in real healthcare services may provide students with hands-on experience on clinical practice and procedures, which are more relevant to their future career practice. Many authorities have suggested that doctors should be produced in real health service system with enhancing community-oriented competencies such as teamwork skills and being a change agent.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Previous studies suggests that medical teaching in service hospitals may also help equip students with better clinical competency as compared to teaching in large university hospitals. 33 - 35 Training in real healthcare services may provide students with hands-on experience on clinical practice and procedures, which are more relevant to their future career practice. Many authorities have suggested that doctors should be produced in real health service system with enhancing community-oriented competencies such as teamwork skills and being a change agent.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely high proportions of graduates practising in rural sites and successfully passing NMLE exhibited that the RTME-GXMU programme has achieved positive early outcomes consistent with other medical education programmes with similar commitment requirements in the USA, 13 14 Australia, 15 16 Japan 17 and Thailand. 18 The above-mentioned foreign medical education programmes have obtained success at different extents in promoting recruitment and retention of the rural physician workforce in their own countries.…”
Section: Discussionmentioning
confidence: 99%
“…If they did, the strategic directions were often confined to one health worker type or targeted at a particular community health issue like maternal health (22,23). The evidence of integrated rural pathways strategies was most developed in Thailand and the Philippines for medical doctors, including at University and early graduate levels (24)(25)(26)(27)(28). There were also examples of step-wise models included Community Health Worker training in Ethiopia (29,30) and international partnerships to boost intelligence and resources for building rural pathways (31).…”
Section: Policy Reviewmentioning
confidence: 99%